Cultural Appropriation for Improved Knowledge Acquisition in Medical Education - Ahmed SA; Hegazy NN; Amin HAA; Ismail MIM; Alakid YF; Kumar AP (Advances in Medical Education and Practice, 2024)
Samar Abdelazim Ahmed,1,2 Nagwa N Hegazy,3 Hebat Allah Ahmed Amin,4 Mariam IM Ismail,5 Yasser Fouad Alakid,6 Archana Prabu Kumar7 1Dubai Medical College for Girls, Dubai, United Arab Emirates; 2Forensic Medicine Department, Faculty of Medicine, Ain Shams University, Cairo, Egypt; 3Family Medicine Department, Faculty of Medicine, Menoufia University (MU), Menoufia, Egypt; 4Pathology Department, Faculty of Medicine, Helwan University, Helwan, Egypt; 5Faculty of Medicine, Delta University, Dakahlia, Egypt; 6Forensic Medicine, Faculty of Medicine, Ain Shams University, Cairo, Egypt; 7Medical Education Department, College of Medicine and Medical Sciences, Arabian Gulf University, Manama, BahrainCorrespondence: Samar Abdelazim Ahmed, Email Prof.samar@dmcg.eduBackground: Culture is an essential component that governs all aspects of human behavior. Superstition is an irrational belief observed in almost all cultures. It is linked to one or more factors like supernatural powers, good luck, bad omen, fiction, illegitimate activity, absurd narration, folk tales, or practice without any rational basis.Methods: A cross-sectional social experiment was conducted to evaluate the effect of cultural appropriation as a tool to enhance medical knowledge acquisition and attitudinal development in medical education. The experiment was designed to target a non-medical population. Four superstition-oriented videos were developed with 20 scientific pieces of information related to forensic medicine. A data collection sheet was developed on Microsoft form with 16 questions was distributed on the participants.Results: Out of the 986 participants, 763 (77.5%) watched the whole set of videos. About 55– 95% of responders demonstrated knowledge acquisition of all the questions. There was a statistically significant difference between those who watched the videos and those who did not. When participants were asked about the most important information they remember from the videos, their answers fell into two main categories; information related to core scientific knowledge (80% of participants) and information not related to the core knowledge (16% of respondents). The top three areas for the reasons why people wanted to watch the videos were curiosity, knowledge, and career. A change in attitudes was reported among the participants where 80% of responders demonstrated curiosity to know more about this world, 46% responders reported developing more respect for the forensic physician and 43% revealed their ignorance about this great hidden world.Conclusion: Cultural appropriation could be a needed strategy to accommodate for upscale in education. Learners might validate that learning happens through a door that adopts not only honours their culture and adapts to it.Keywords: contextualization, knowledge acquisition, medical education